2023
DOI: 10.1136/jnnp-2022-330296
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an outpatient rehabilitation programme in patients with neuralgic amyotrophy and scapular dyskinesia: a randomised controlled trial

Abstract: BackgroundNeuralgic amyotrophy (NA) is an acute inflammation of nerves within the brachial plexus territory leading to severe pain and multifocal paresis resulting in >60% of patients having residual complaints and functional limitations correlated with scapular dyskinesia. Our primary aim was to compare the effects of multidisciplinary rehabilitation (MR), focused on motor relearning to improve scapular dyskinesia and self-management strategies for reducing pain and fatigue, with usual care (UC) on shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The other study suggested a multidisciplinary rehabilitation program according to patient's needs and goals. The program was shown to improve participants' functional capability with minimal pain [8]. In that study, however, the participants were older than 18 years and had more than 8 weeks after onset.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The other study suggested a multidisciplinary rehabilitation program according to patient's needs and goals. The program was shown to improve participants' functional capability with minimal pain [8]. In that study, however, the participants were older than 18 years and had more than 8 weeks after onset.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies report that an immunotherapy could be effective for pain control and neurologic recovery. Additionally, a multidisciplinary rehabilitation program is suggested for functional improvement and reduction of musculoskeletal complications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in the literature, the rehabilitation process lacks certainty, but some elements seem effective and are widely used, such as neurodynamic techniques [ 20 ]. Recent studies have shown that a multidisciplinary approach appears valid in managing these patients, emphasizing the importance of sensorimotor recovery, including exercises for regaining upper limb proprioceptive abilities and motor imagery [ 9 , 10 ]. A factor that had a positive influence on the patient’s prognosis in this case report is his young age, motivation, active lifestyle, and adherence to the therapeutic plan (the patient attended all the scheduled sessions).…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is crucial since 60% of patients have residual weakness 2–3 years after the onset of the disease; over 50% are limited by pain; 63% experience severe fatigue; and 82% face difficulties in daily activities [ 8 ]. Several strategies have recently been proposed for the rehabilitation of PTS patients, such as a structured multidisciplinary approach that has proven effective [ 9 , 10 ]. This case report shows, for the first time, through an objective strength evaluation system, how recovery can occur even after three years and the role that a progressive multimodal rehabilitation treatment can have in achieving outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although rotatory movements of the scapula and other abnormal involuntary movements of the shoulder are typical manifestations of dystonic tics in patients with Tourette syndrome, shoulder involuntary movements may be peripherally induced. One cause of shoulder (scapular) dyskinesia is neuralgic amyotrophy [117]. This condition, manifested by episodes of acute pain in the proximal arm, presumably due to acute autoimmune inflammation of the nerves in the brachial plexus, is often associated with abnormal involuntary movements of the shoulder.…”
Section: Miscellaneous Peripherally-induced Movement Disordersmentioning
confidence: 99%